2022
DOI: 10.1039/d2qi00854h
|View full text |Cite
|
Sign up to set email alerts
|

The excellent electromagnetic wave absorbing properties of carbon fiber composites: the effect of metal content

Abstract: In this work, the effect of metal loading on electromagnetic (EM) absorbing performance was investigated to obtain an excellent EM absorber through a simple process. Specifically, iron/cobalt/carbon nanocomposite fibers were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In particular, the RCS reduction value of CS-3 at 0° was 23.0 dBm 2 , indicating the strongest attenuation effect. This finding was consistent with the results of the EM-wave absorption performance of the material, revealing that the material losses occurred in the same way …”
Section: Resultssupporting
confidence: 91%
“…In particular, the RCS reduction value of CS-3 at 0° was 23.0 dBm 2 , indicating the strongest attenuation effect. This finding was consistent with the results of the EM-wave absorption performance of the material, revealing that the material losses occurred in the same way …”
Section: Resultssupporting
confidence: 91%
“…This means that their electromagnetic waves are absorbed by electrons in the metal or propagated back in the same direction. At the same time, some of its electromagnetic energy is lost as heat [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…67 Finally, metal matrix absorbers are multiphase materials composed of ductile metal or alloy, which could also implant some nanosized reinforcement materials. Guo et al 68 prepared an excellent metal matrix iron/cobalt/carbon EMWA nanocomposite through electrospinning and the heat-treatment method. The results indicated that the combination of magnetic metal particles and carbon components could achieve an optimal wave absorption performance, while accompanied with high-temperature resistance.…”
Section: Advantages Of 1d Nanomaterials For Microwave Absorptionmentioning
confidence: 99%